The Role of SMEs in Indonesian E-Commerce to the Indonesian Economy during the Covid-19 Pandemic - Wijanarka, Tunjung; Sari, Ni Kadek Dias Anggun Purnama (Journal of World Trade Studies, 2022)
Globalization and technological advancements increasingly provide a fresh approach for economic growth through economic digitalisation, one of which is the e-commerce business. In this study, the authors state that digitalisation in trade has had a positive impact on the growth of SMEs in Indonesia, which has contributed to the country’s economic climate. As a result, the authors attempt to explain the role of SMEs through Indonesian e-commerce and how they affected the Indonesian economy during the Covid-19 pandemic through a qualitative research. The authors chose the Covid-19 pandemic as a time period for this research as the growth of SMEs through the e-commerce business experienced significant growth during the pandemic. This growth was primarily caused by the ongoing pandemic conditions, which rendered traditional economic activities impossible. Finally, the role of SMEs in ecommerce contributed positively to the Indonesian economy during the Covid-19 pandemic.